Conserved Non-Coding Sequences are Associated with Rates of mRNA Decay in Arabidopsis - Spangler, Jacob B.; Feltus, Frank A. (Frontiers in Plant Science, 2013)
Steady-state mRNA levels are tightly regulated through a combination of transcriptional and post-transcriptional control mechanisms. The discovery of cis-acting DNA elements that encode these control mechanisms is of high importance. We have investigated the influence of conserved non-coding sequences (CNSs), DNA patterns retained after an ancient whole genome duplication event, on the breadth of gene expression and the rates of mRNA decay in Arabidopsis thaliana. The absence of CNSs near α duplicate genes was associated with a decrease in breadth of gene expression and slower mRNA decay rates while the presence CNSs near α duplicates was associated with an increase in breadth of gene expression and faster mRNA decay rates. The observed difference in mRNA decay rate was fastest in genes with CNSs in both nontranscribed and transcribed regions, albeit through an unknown mechanism. This study supports the notion that some Arabidopsis CNSs regulate the steady-state mRNA levels through post-transcriptional control mechanisms and that CNSs also play a role in controlling the breadth of gene expression.